The in vitro Effect of Irrigants with Low Surface Tension on Enterococcus faecalis - Giardino, Luciano; Estrela, Carlos; Generali, Luigi; Mohammadi, Zahed; Asgary, Saeed (Iranian Endodontic Journal, 2015)
Introduction: Due to the complex anatomy of the root canal system and high surface tension of common root canal irrigants (RCI), conducting an investigation on RCIs containing surfactants is a priority. The aim of this in vitro study was to verify the antibacterial potential of RCI with low surface tension in root canals infected with Enterococcus faecalis (E. faecalis). Methods and Materials: Thirty-five extracted human maxillary anterior teeth were prepared and inoculated with E. faecalis for 60 days. After root canal preparation, the teeth were randomly divided to one positive and one negative control groups and 5 experimental groups: Hypoclean/Tetraclean NA, Hypoclean, Tetraclean, NaOCl/Tetraclean and NaOCl. Bacterial growth was observed by turbidity of culture medium and then measured using a UV spectrophotometer. Data were analyzed in three time intervals (pre-instrumentation and, 20 min and 72 h after canal preparation) using the ANOVA and post hoc Tukey’s tests. The level of significance was set at 0.05. Results: The results indicated the presence of E. faecalis in all post-irrigation samples irrespective of the RCI. However, the optical densities in both post-irrigation periods showed bacterial reduction and significant differences between groups. Conclusion: RCI with low surface tension showed antibacterial potential in E. faecalis infected roots. Keywords: Enterococcus faecalis; Hypoclean; Sodium Hypochlorite; Tetraclean